THE INFLUENCE OF NATURAL PIGMEN ADDITION IN FEED TO COLOR BRIGHTNESS AND GROWTH OF JUVENILE KOI (CYPRINUS CARPIO) - Laili Apriana Nur; Mita Ayu Liliyanti; L.A.T.T.W. Sukmaring Kalih (Fakultas Perikanan Universitas 45 Mataram, 2020)
Koi fish (Cyprinus carpio) is a freshwater ornamental fish that is popular with people today. The attractiveness of koi fish can be measured by its brilliant color and health or stamina. The brightness of color in ornamental fish can be improved by providing feed containing carotenoids. Carrots (Daucus carrota), pumpkin (Cucurbita moschata), sweet potatoes (Ipomoea batatas) and gumitir flowers (Tagetes spp.) Are some natural carotenoid sources that are thought to increase the brightness of ornamental fish. The purpose of this study was to determine the effect of the addition of natural pigments in feed on the brightness and growth of koi (C. carpio) seeds. This study used a Completely Randomized Design (CRD) with an experimental method of 5 treatments (P1, P2, P3, P4, P5) and 3 replications. P1 = ordinary pellet feed, P2 = addition of carrot flour, P3 = addition of pumpkin flour, P4 = addition of sweet potato flour, P5 = addition of gumitir flour. The results showed that pumpkin flour (P3) was the most effective ingredient in increasing the brightness of koi fish. The addition of pumpkin flour to the feed can also increase growth in weight and length. This value is the best value among all treatments.